Prevalence and influencing factors of abnormal carotid artery intima-media thickness in Henan Province in China - Yang, Tingting; Wang, Yating; Zhang, Xiaoke; Xiang, Siyun; Wen, Jing; Wang, Wen; Guan, Ke; Wang, Weixiang; Yang, Yang; Hao, Liuwei; Chen, Yongchun (Frontiers in Endocrinology, 2023)
Background Carotid intima-media thickness (CIMT) has been shown to be a valuable predictor of cardiovascular diseases (CVDs). The aim of this study was to investigate the influencing factors of CIMT among adults in Central China. Methods A total of 2,578 participants who underwent physical examination in Henan Provincial People’s Hospital between January 2018 and July 2018 were enrolled. The respondents were divided into two subgroups according to their CIMT value (CIMT ≥1.0 mm group and CIMT <1.0 mm group). Variables considered were age, gender, total cholesterol, triglycerides, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) triglycerides, fasting blood glucose, and uric acid levels, as well as hypertension, diabetes, body mass index (BMI), waist-to-hip ratio, body fat percentage, and visceral fat area (VFA). Logistic regression analysis was performed to explore the potential factors influencing CIMT. Results The proportion of CIMT ≥1.0 mm among the physical examination population was 27.42% (707/2 578). The analysis of the two groups revealed significant differences in age, sex, hypertension, diabetes, total cholesterol, and HDL cholesterol. In the logistic regression analysis, age (OR=1.071, 95%CI=1.062–1.080), male sex (OR=2.012, 95%CI=1.251–2.238), hypertension (OR=1.337, 95%CI=1.031–1.735), diabetes (OR=1.535, 95%CI=1.045–2.255), HDL cholesterol (OR=0.540, 95%CI=0.366–0.796), and LDL cholesterol (OR=1.336, 95%CI=1.154–1.544) were significantly associated with abnormal CIMT. Conclusion Early screening should be carried out among men, the older adults, and those with hypertension, diabetes, and dyslipidemia.